جدلية العلاقة بين الفقر والعبودية وبعض مؤشراتها الحديثة دراسة في الجغرافية السياسية - ياسر الياسري حميد (Journal of College of Education, 2019)
Slavery is an ancient phenomenon that dates back to the beginning of the emergence of agricultural societies. The laws of heaven and status of successive states and governments have given special significance for this issue. That is because they represent a political, social, economic and moral departure from the human values. Despite the criminalization of the phenomenon of slavery by international organizations, it still active in the global communities. However, this study came to illustrate this phenomenon and show the link between the phenomenon of poverty and servitude and to show some recent indicators of slavery.